Replacement of Dicalcium Phosphate with Diammonium Phosphate in the Diet and Its Effect on Nutrient Utilization and Milk Production in Lactating Crossbred Cattle - Sharma, Ritu; Tiwari, D.P.; Mondal, B.C.; Kumar, Anil (Indian Journal of Animal Nutrition, 2018)
Lactating crossbred cows (15) in mid lactation were assessed for their performance after feeding mineral mixture containing diammonium phosphate (DAP) in replacement of dicalcium phosphate (DCP) at differentlevels. Cows were divided into three groups of five each in such a way that the average milk yield in all the groups was similar. The animals in group 1 were fed ration containing mineral mixture with 0% DAP while those in groups 2 and 3 were fed ration with mineral mixture containing 50 and 100% DAP, respectively by replacing DCP on P content basis. There was no significant effect on the milk yield, milk composition in terms of total solids, fat, protein, lactose, ash, SNF, calcium, phosphorus and gross energy content, gross and net energeticefficiencies and gross and net efficiency of nitrogen utilization for milk production, body weight changes, feed intake and digestibility of nutrients. The values of blood biochemical parameters viz., serum total protein, albumin and globulin contents, serum alkaline phosphatase, alanine amino transferase and aspartate amino transferase, Ca and P were similar in all the groups. However, the digestibility of ether extract was lower (P